Filariasis of the Breast in a Pregnant Woman Diagnosed by Fine-needle Aspiration Cytology: A Case Report. Issue 6 (1995) - Lau, Melanie; Tauchi, Pamela; Kim, Milton; Liu, Francis; Namiki, Thomas
Abstract : Background: Despite increased immigration to the United States from endemic areas, the diagnosis of microfilariasis in this country remains infrequent. This disease may occasionally present as a breast mass, in the absence of other clinical findings. Case: We report an unusual case of Wuchereria bancrofti diagnosed in a pregnant woman by breast fine-needle aspiration (FNA) and discuss the clinical implications of filariasis in pregnancy. Conclusion: FNA is safe and reliable in pregnancy. Infants of mothers with breast filariasis should be monitored.